Hidden on both sides of the Alps: Rubus noricus, a new species of bramble (Rosaceae) from Austria and Germany - Hohla, Michael; Pagitz, Konrad; Király, Gergely (Phytotaxa, 2021)
Rubus ser. Rhamnifolii includes apomictic polyploid species, which occur in north-western and central Europe, with rare outposts to eastern central Europe. A regionally distributed tetraploid species of the series occurring north and south of the Eastern Alps in Austria and Germany, Rubus noricus is described here. The new species is morphologically compared with similar taxa of the series, moreover, comprehensive iconography, data on distribution and ecology are presented.